(untitled) - 1943-; Altman, Linda Jacobs (New York, 1999)
Describes the characteristics and behavior of small dogs in general, also discussing the physical appearance and place in history of some specific breeds.
Includes bibliographical references (p. ).
Keywords: Dogs; Juvenile literature; Dogs